Monitoring spatial and temporal variations of phosphorus within a cold climate subsurface flow constructed wetland. Issue 1 (1st January 2004) - McCarey, A E.D; Anderson, B C; Martin, D
Abstract : Performance of constructed wetland systems has been widely variable, particularly with respect to cold climate systems. Phosphorus removal has been particularly challenging in wetland systems, with widely variable removal efficiencies being reported. A subsurface flow constructed wetland is being used at Sunny Creek Estates in Bayside, Ontario, to polish sewage lagoon effluent. A benchmarking study was conducted to gather operational data from within the wetland, to characterize phosphorus dynamics within the system. Samples were collected and analyzed for total and dissolved phosphorus concentrations for a one-year period. Spatial and temporal variations in phosphorus were then investigated, and mass balances were performed. Mass balances conducted on an average annual basis, and on a seasonal basis, indicated a net removal of phosphorus in all cases except the spring season. Segmented phosphorus profiles through the wetland revealed that, regardless of season, there is more phosphorus in shallower wells, and with increasing distance from the influent distribution pipe. Phosphorus masses varied significantly with depth, and in directions both parallel and perpendicular to flow through the wetland. The seasonal and spatial variations illustrate the importance of monitoring within wetlands, and reinforce the limitations of using a black box approach in wetland design. Key words : constructed treatment wetlands, subsurface flow, wastewater treatment, phosphorus, cold-climate operation, eutrophication, seasonal variability.